Optimizing 21st Century Skills Through Island-based Physics Multirepresentation Learning at Madrasah Aliyah Negeri 1 Maluku Tengah School - Jamaludin, Jamaludin; Latununuwe, Altje; Rachman, Gazali; Dulhasyim, Ashari Bayu P. (Pascasarjana Universitas Mataram, 2025)
In the current era of globalization, prioritizing four basic skills such as critical thinking, collaboration, communication, and creativity, is needed to prepare students to live in the future. This community service activity aims to optimize these skills through the application of ocean-island-based physics multirepresentation learning, which is relevant to the living environment of students in Central Maluku. The multirepresentation approach helps students understand abstract physics concepts through various forms of representation, such as visual, mathematical, and verbal, which encourages deeper understanding. The context of the sea-island environment, such as currents, waves, and hydrostatic pressure, is used as physics teaching material to increase the relevance and motivation of student learning, as students can see how physics concepts are integrated in their daily lives. The service method used includes observation, teacher training, and implementation of contextual learning based on sea-islands. The results showed that teachers who participated in the training were able to design and implement contextualized multirepresentation physics learning, which is relevant to the local sea-island environment. Students also responded positively and showed improvement in 4C skills through the island sea-based learning process and this learning is expected to continue to evolve and be applied in various learning contexts to advance 21st century skills among students